Student Worksheet Based on Contextual Teaching and Learning (CTL) in Biology Learning related Ecosystem Concept - Rohman, Muhammad Milatur (Islamic Journal of Integrated Science Education (IJISE), 2023)
This study aims to determine the concept, feasibility and effectiveness of student worksheet based on contextual teaching and learning (CTL) in biology learning related ecosystem concept. This research uses research and development with the ADDIE (Analysis-Design-Development-Implement-Evaluate) model. The subjects of this study were validators (one expert lecturers and two biology teachers) and seventh grade students of Nusa Penida Private Junior High School Medan. The object of this research is student worksheet based on CTL in biology teaching materials on ecosystem learning materials at Nusa Penida Private Junior High School Medan. The research instrument used in this study was a questionnaire to obtain student worksheet product validation assessment data. Technical analysis of the data in this study using expert feasibility test and effectiveness analysis. The results showed that the student worksheet based on CTL was feasible to use with a feasibility level of the learning outcomes test sheet of 93.1% and a student worksheet eligibility rate of 83%.The results of the analysis of student learning mastery show that the student worksheet based on CTL in ecosystem concept categorized as complete in the completeness of thinking ability indicators with a percentage gain of 84.3%. Thus, the student worksheet based on CTL in biology learning related ecosystem concept that has been developed is feasible for use in biology learning and is effective in developing students' thinking skills.